A MAJOR POLYPEPTIDE OF CHLOROPLAST MEMBRANES OF CHLAMYDOMONAS REINHARDI : Evidence for Synthesis in the Cytoplasm as a Soluble Component - Hoober, J. Kenneth (The Rockefeller University Press, 1972)
Electrophoresis of thylakoid membrane polypeptides from Chlamydomonas reinhardi revealed two major polypeptide fractions. But electrophoresis of the total protein of green cells showed that these membrane polypeptides were not major components of the cell. However, a polypeptide fraction whose characteristics are those of fraction c (a designation used for reference in this paper), one of the two major polypeptides of thylakoid membranes, was resolved in the electrophoretic pattern of total protein of green cells. This polypeptide could not be detected in dark-grown, etiolated cells. Synthesis of the polypeptide occurred during greening of etiolated cells exposed to light. When chloramphenicol (final concentration, 200 µg/ml) was added to the medium during greening to inhibit chloroplastic protein synthesis, synthesis of chlorophyll and formation of thylakoid membranes were also inhibited to an extent resulting in levels of chlorophyll and membranes 20–25% of those found in control cells. However, synthesis of fraction c was not affected by the drug. This polypeptide appeared in the soluble fraction of the cell under these conditions, indicating that this protein was synthesized in the cytoplasm as a soluble component. When normally greening cells were transferred from light to dark, synthesis of the major membrane polypeptides decreased. Also, it was found that synthesis of both subunits of ribulose 1, 5-diphosphate carboxylase was inhibited by chloramphenicol, and that synthesis of this enzyme stopped when cells were transferred from light to dark.